Fertility-Preserving Treatments and Patient- and Parental Satisfaction on Fertility Counseling in a Cohort of Newly Diagnosed Boys and Girls with Childhood Hodgkin Lymphoma - Drechsel, Katja C E; IJgosse, Irene M; Slaats, Sofie; Raasen, Lisanne; Stoutjesdijk, Francis S; van Dulmen-den Broeder, Eline; Wallace, W Hamish; Beishuizen, Auke; Körholz, Dieter; Mauz-Körholz, Christine; Cepelova, Michaela; Uyttebroeck, Anne; et al. (Cancers, 2024)
PURPOSE: The purpose of this study is to evaluate the use of fertility-preserving (FP) treatments and fertility counseling that was offered in a cohort of newly diagnosed children with classical Hodgkin lymphoma (cHL). METHODS: In this observational study, boys and girls with cHL aged ≤ 18 years with scheduled treatment according to the EuroNet-PHL-C2 protocol were recruited from 18 sites (5 countries), between January 2017 and September 2021. In 2023, a subset of Dutch participants (aged ≥ 12 years at time of diagnosis) and parents/guardians were surveyed regarding fertility counseling. RESULTS: A total of 101 boys and 104 girls were included. Most post-pubertal boys opted for semen cryopreservation pre-treatment (85% of expected). Invasive FP treatments were occasionally chosen for patients at a relatively low risk of fertility based on scheduled alkylating agent exposure (4/5 testicular biopsy, 4/4 oocyte, and 11/11 ovarian tissue cryopreservation). A total of 17 post-menarchal girls (20%) received GnRH-analogue co-treatment. Furthermore, 33/84 parents and 26/63 patients responded to the questionnaire. Most reported receiving fertility counseling (97%/89%). Statements regarding the timing and content of counseling were generally positive. Parents and patients considered fertility counseling important (94%/87% (strongly agreed) and most expressed concerns about (their child's) fertility (at diagnosis 69%/46%, at present: 59%/42%). CONCLUSION: Systematic fertility counseling is crucial for all pediatric cHL patients and their families. FP treatment should be considered depending on the anticipated risk and patient factors. We encourage the development of a decision aid for FP in pediatric oncology.